Pemikiran Hukum Islam Tentang Persatuan Warga Negara Prespektif Piagam Madinah, Pancasila, dan UUD 1945 - Ningsih, Fitri; Hilal, Fatmawati; Sultan, Lomba (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article explains how Islamic legal thought particularly through the Medina Charter, Pancasila and the 1945 Constitution contributed to the concept of citizens’ unity. To capture that point, this article will focus on three main discussions. First, the charter of Medina and Islamic legal thought on unity. Second, panchayat and the 1945 Constitution on unity. Third, a comparison of the concept of unity of the Medina Charter, Pancasila, and the Constitution of 1945. The Medina Charter is a milestone that shows how Islam from the beginning has laid the foundation for a composite society. This document was not just a treaty, but rather the first written constitution that recognized the rights and obligations of every group in Medina, including non-Muslims. Such principles as freedom of religion, guarantee of security, and the obligation of mutual assistance in the face of common threats, became tangible evidence of Islam’s commitment to unity in the midst of diversity. In the perspective of Islamic law, the Medina Charter asserts that differences are not barriers to unity, but rather the potential for strength if managed with the principles of justice and tolerance.